Joyce Carol Oates, Small-Press Author. - Biederman, Lucy (Contemporary Literature)
The article examines writer Joyce Carol Oates's career as a lens on the shift from independent publishers to conglomerates, focusing on her move from Vanguard to larger corporate houses amid changing literary markets. Topics include transformations in U.S. publishing, Oates's conflicted relationships with her publishers, and tensions between artistic recognition and commercial success.